Body mass index, adiposity rebound and early feeding in a longitudinal cohort (Raine Study) - Chivers, P.; Hands, B.; Parker, H.; Bulsara, Max; Beilin, L.; Kendall, Garth; Oddy, W. (Nature Publishing Group, 2010)
Objective: This study examined the influence of type and duration of infant feeding on adiposity rebound and the tracking of body mass index (BMI) from birth to 14 years of age.